Republic of Korea : Report on the Observance of Standards and Codes. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses key findings of the Report on the Observance of Standards and Codes for the Republic of Korea. Responsibilities, objectives, and powers related to banking supervision are clearly defined in the Republic of Korea. The legal framework currently in place reasonably provides the necessary powers to authorize the establishment of banks, conduct ongoing supervision, address compliance with laws and regulations, as well as undertake corrective actions to address safety and soundness concerns. Authorization processes are generally thorough but there is room to require formal approval for certain activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet